A novel species in the genus Heveochlorella (Trebouxiophyceae, Chlorophyta) witnesses the evolution from an epiphytic into an endophytic lifestyle in tree-dwelling green algae - Ma, Shuai; Huß, Volker; Tan, Deguan; Sun, Xuepiao; Chen, Jingbo; Xie, Yaoyun; Zhang, Jiaming (European Journal of Phycology, 2013)
Roystonea regia is a popular landscape palm famous for its smoothly sculpted white trunk, but sometimes it is spoiled by epiphytic green algae inhabiting the bark. We identified a trebouxiophycean green alga as the single dominant species growing on the trunk of a royal palm in Hainan, China. Light and transmission electron microscopy showed adult cells to be spherical with a diameter of 6.4-13.7 μm, and to contain a single cup-shaped parietal chloroplast. Each chloroplast contained a pyrenoid of 1.4-2.1 μm in diameter. The pyrenoid was penetrated by radially arranged tubular invaginations surrounded by pyrenoglobuli, which is similar to Heveochlorella hainangensis. Phylogenetic analyses inferred from nuclear-encoded 18S rRNA sequences placed strain ITBB A3-8 in the Watanabea clade (Trebouxiophyceae, Chlorophyta), closely related to H. hainangensis. But strain ITBB A3-8 differs sufficiently from H. hainangensis in significant aspects of ultrastructure, physiology, and nuclear and plastid ribosomal RNA and ITS sequences to be treated as a novel species, H. roystonensis Shuai Ma, V. Huss, Xuepiao Sun & Jiaming Zhang, sp. nov. The growth of the epiphytic H. roystonensis seems to be promoted by air pollution in the city, while the endophytic H. hainangensis requires an organic carbon source for optimal growth. Thus in the genus Heveochlorella both an epiphytic and an endophytic lifestyle of tree-dwelling green algae can be observed. © 2013 British Phycological Society.
Keywords: Epiphytic algae; Heveochlorella hainangensis; Heveochlorella roystonensis sp. nov.; ITS; pyrenoid; SSU rRNA gene phylogeny; Trebouxiophyceae; taxonomy